The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjopen-2021-056270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leisure-time physical activity in controlling hypertension: a systematic review and meta-analysis protocol

Abstract: IntroductionHypertension is a major risk factor for cardiovascular diseases. In 2015, over 1.13 billion individuals worldwide had hypertension. Globally, it results in 10.8 million deaths every year. Around half of the individuals do not continue treatment with medicine to control blood pressure. Physical activity, a non-pharmacological option of treatment, reduces blood pressure. We aim in this research to examine the effect of leisure-time physical activity in controlling blood pressure.Methods and analysisW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
5
1
1
Order By: Relevance
“…This study is registered on PROSPERO (CRD42021260751). The protocol of this study has been published in a peer-reviewed journal 45 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is registered on PROSPERO (CRD42021260751). The protocol of this study has been published in a peer-reviewed journal 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Interventions conducted to prevent hypertension were excluded. Details of the study selection criteria are in Appendix p. 6 and our published protocol 45 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, another study reported body composition variables BMI, WC and BF% also mediated the relationship between CRF and BP in cohort of young adults [23]. A meta-analysis of experimental randomized control trials revealed improvements in moderate-intensity leisure-time physical activity was associated with significant reduction in both SBP and DBP [24]. Further, a meta-analysis of weight-reduction randomized control trials reported a 4-kilogram weight reduction was associated with 6 mmHg reduction in SBP [25].…”
Section: Discussionmentioning
confidence: 97%
“…Second, people in LMICs, particularly those living in rural areas, might not engage in leisure-time PA as much as people in high-income countries do while they might engage in occupational PA much more than people in high-income countries. Thus, the PA–hypertension association in LMICs might not be necessarily similar to those observed in high-income countries [ 11 , 12 ]. Interestingly, in a prospective cohort study in Mexico, higher moderate to vigorous PA (MVPA) at the workplace was associated with a lower hypertension risk [ 13 ], which contrasted with the observations in high-income countries.…”
Section: Introductionmentioning
confidence: 99%